The E3 ligase HECTD4 regulates COX-2-dependent tumor progression and metastasis - Joanna A. Vuille; Cem Tanriover; Ezgi Antmen; Douglas S. Micalizzi; Richard Y. Ebright; Sambhavi Animesh; Robert Morris; Soroush Hajizadeh; Zachary J. Nicholson; Hunter C. Russell; Eric F. Zaniewski; Ben S. Wittner; et al. (Proceedings of the National Academy of Sciences, 2025)
E3 ubiquitin ligases mediating turnover of proteins engaged in cancer progression point to key regulatory nodes. To uncover modifiers of metastatic competency, we conducted an in vivo genome-wide CRISPR-inactivation screen using cultured breast circulating tumor cells, following intravascular seeding and lung colonization. We identified HECTD4, a previously uncharacterized gene encoding a conserved potential homologous to E6AP C-terminus domain–containing ubiquitin transferase, as a potent tumor and metastasis suppressor. We show that purified HECTD4 mediates ubiquitin conjugation in vitro, and proteomic studies combined with ubiquitin remnant profiling identify a major degradation target as the prostaglandin synthetic enzyme cyclooxygenase-2 ( COX-2 ; PTGS2 ). In addition to COX-2 itself, HECTD4 targets its regulatory kinase MKK7. In breast cancer models, HECTD4 expression is induced as cells lose adherence to the matrix, and its depletion massively increases COX-2 expression, enhancing anchorage-independent proliferation and tumorigenesis. Genetic or pharmacologic suppression of COX-2 reverses the protumorigenic and prometastatic phenotype of HECTD4-depleted cells. Thus, HECTD4 encodes an E3 ubiquitin ligase that downregulates COX-2 suppressing anchorage independence in epithelial cancer cells.